I'm trying to simplify this expression with Mathematica.

$$\sqrt{2-a^2-2\sqrt{1-a^2}}, 0

It can be simplified as

$$\sqrt{1+1-a^2-2\sqrt{1-a^2}}=\sqrt{(1-\sqrt{1-a^2})^2}=1-\sqrt{1-a^2}$$

denesting original radical. I used the command

FullSimplify[Sqrt[2 - a^2 - 2 Sqrt[1 - a^2]], 0 < a < 1]


but it doesn't work.

Any idea?

Try this:

Simplify[Sqrt[2 - a^2 - 2 Sqrt[1 - a^2]] /. a^2 -> 1 - x] /.
x -> 1 - a^2

(*  Sqrt[(-1 + Sqrt[1 - a^2])^2]   *)


Have fun!

• Include assumption Simplify[Sqrt[2 - a^2 - 2 Sqrt[1 - a^2]] /. a^2 -> 1 - x, 0 < x < 1] /. x -> 1 - a^2 Nov 27, 2018 at 15:04
Reduce[Reduce[y == Sqrt[2 - a^2 - 2 Sqrt[1 - a^2]] && 0 < a < 1, a, Reals], y, Reals]


or

FullSimplify[Sqrt[2 - a^2 - 2 Sqrt[1 - a^2]],
TransformationFunctions -> {Reduce[Reduce[y == # && 0 < a < 1, a, Reals], y, Reals] &}]


0 < a < 1 && y == 1 - Sqrt[1 - a^2]

Sqrt[2-a^2-2 Sqrt[1-a^2]] /. Sqrt[a_ + b : k_. Sqrt[x_]]:>
Sqrt[(a+Sqrt[a^2-b^2])/2]+Sign[k] Sqrt[(a-Sqrt[a^2-b^2])/2] // Simplify[#,0<a<1]&


1 - Sqrt[1 - a^2]